2013
DOI: 10.4103/0973-8258.116396
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant activity of essential oil from Ajwain (Trachyspermum ammi) seeds

Abstract: Background: Free radicals provoke chain reactions within the cell and cause damage to the cell. Oxidation of bio molecules such as carbohydrate, protein, lipid and nucleic acid leads to the production of free radicals which induce the onset of disease. Antioxidants scavenge these free radicals, thereby protecting the cell from damage. Phenolic compounds found in varieties of seeds and fruits are thought to have antioxidant activities. Aim: The present study was designed to examine the in vitro antioxidant acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…In another study, the antioxidant activity of the C. copticum essential oil was assessed by comparison of ferric reducing antioxidant power, activity of DPPH, (Farinacci et al, 2008) Improvement of immune function in pigs' gut (Li et al, 2012) Induce immunosuppressive effect (Amirghofran et al, 2011) Modifying immune response (Hashemipour et al, 2013) Carvacrol Suppression of autoimmune arthritis (Spiering et al, 2012) Beneficial effects on innate immune conditions (Giannenas et al, 2012) Modulation of Th1/Th2 ratio Beneficial effect in improvement of inflammatory disorders Increase of FOXP3 expression (marker of regulatory T cells) and modulation of immune system (Burt et al, 2007) Modifying immune response (Hashemipour et al, 2013) and H 2 O 2 radical scavenging with ascorbic acid. Results of this study showed that C. copticum can be applied in foodstuff and can be used for medicinal purposes as non-synthetic antioxidant agent (Chatterjee et al, 2013).…”
Section: Antioxidant Propertiesmentioning
confidence: 83%
See 1 more Smart Citation
“…In another study, the antioxidant activity of the C. copticum essential oil was assessed by comparison of ferric reducing antioxidant power, activity of DPPH, (Farinacci et al, 2008) Improvement of immune function in pigs' gut (Li et al, 2012) Induce immunosuppressive effect (Amirghofran et al, 2011) Modifying immune response (Hashemipour et al, 2013) Carvacrol Suppression of autoimmune arthritis (Spiering et al, 2012) Beneficial effects on innate immune conditions (Giannenas et al, 2012) Modulation of Th1/Th2 ratio Beneficial effect in improvement of inflammatory disorders Increase of FOXP3 expression (marker of regulatory T cells) and modulation of immune system (Burt et al, 2007) Modifying immune response (Hashemipour et al, 2013) and H 2 O 2 radical scavenging with ascorbic acid. Results of this study showed that C. copticum can be applied in foodstuff and can be used for medicinal purposes as non-synthetic antioxidant agent (Chatterjee et al, 2013).…”
Section: Antioxidant Propertiesmentioning
confidence: 83%
“…Results of this study showed that C . copticum can be applied in foodstuff and can be used for medicinal purposes as non‐synthetic antioxidant agent (Chatterjee et al ., ).…”
Section: Antioxidant Propertiesmentioning
confidence: 97%
“…The antioxidant capacity of plants is clearly associated with the activity of "free radical scavenging enzymes". The antioxidant potential is inversely proportional to the IC 50 value, i.e., lower the IC 50 value it indicates high antioxidant activity and vice versa (Chatterjee et al, 2013).…”
Section: Antioxidant Assay (Dpph Method)mentioning
confidence: 99%
“…It also possesses antimicrobial, nematicidal, antihelminthic, antifilarial activities. [ 7 ] The essential oil (2.5% to 5% in the dried fruits) is dominated by thymol (35% to 60%) furthermore, α-pinene, p-cymene, limonene, which majorly contributes to its curative properties. [ 8 ] T. ammi commonly known as ajwain was selected to evaluate its anti-JE activity in vitro .…”
Section: Introductionmentioning
confidence: 99%